Wawasan Al-Quran Tentang Kesetaraan Gender - Adam, Adiyana; Haddade , Hasyim; Damis, Rahmi (STIT Muhammadiyah Paciran Lamongan, 2022)
The discussion about gender is getting wider, meanwhile the misunderstandings about the meaning of gender are still exist, especially based on Islamicperspective. The debate about the pros and cons of gender equality is extremely debated. Not a few think that gender equality in Islam is prohibited even though Islam also places women in the best possible position. In this study, the author examines how the Qur'an insight regarding to gender equality. Through a qualitative method approach, the researcher tried to examine through the Qur‟an and the interpretation of related issues. The results show that through theverses of the Qur'an it does not differentiate between men and women in various aspects. This can be seen in various statements of the Qur'an which always equalize the position of men and women, its regard to their human nature. The difference between men and women is only limited to differences in human nature.